Peculiarities of spectral parameters of EEG, HRV and routine parameters of immunity in patients with various levels of the entropy of EEG, HRV, immunocytogram and leukocytogram - Popadynets’, O O; Gozhenko, A I; Zukow, W; Popovych, I L (Journal of Education, Health and Sport, 2019)
Background. We have previously shown that the entropy levels of spectral parameters of EEG and HRV as well as of Immunocytogram and Leukocytogram are well dispersed. The method of cluster analysis was the distribution of the observed contingent into four groups that are homogeneous in terms of entropy. Have been identified the spectral parameters and indices of HRV, the amplitude-frequency and spectral parameters of the rhythms of EEG as well as the indices of asymmetry and lateralization of rhythms, which together are four clusters of entropy significantly different from each other. The purpose of this study is to identify the recognition parameters of immunity together with spectral parameters of EEG and HRV. Material and methods. In basal conditions in 37 men and 14 women with chronic pyelonephritis and cholecystitis in remission as well as without clinical diagnose but with dysfunction of neuro-endocrine-immune complex and metabolism, we recorded twice, before and after balneotherapy at the spa Truskavets’, EEG (“NeuroCom Standard”) and HRV (“Cardiolab+VSR”). In blood we determined parameters of Immune status on a set of I and II levels recommended by the WHO. Than we calculated for each locus of EEG and HRV as well as for Immunocytogram and Leukocytogram the Entropy (h) using Shannon’s formula. Results. The cluster analysis method created four groups, homogeneous in entropy parameters. Discriminant analysis revealed 25 SPD of EEG parameters, 5 HRV parameters, and 9 immunity parameters, by the totality of which four entropy clusters clearly different from each other. Conclusion. Quantitatively and qualitatively different levels of entropy of the spectral parameters of EEG and HRV as well as the Immunocytogram and Leukocytogram are accompanied by characteristic constellations of the parameters of EEG, HRV and Immunity.